The Effect Of Due Professional Care, Objectivity, Audit Fee And Time Budget Pressure On Audit Quality With Auditor Ethics As Moderating Variable - Danita, Irna; Sandakila, Feldo Ferdio (Riau International Conference on Economics, Business and Accounting, 2025)
This study aims to determine: (1) the effect of Due professional Care on Audit Quality, (2) the effect of Objectivity on Audit Quality, (3) the effect of Audit Fee on Audit Quality, (4) the influence of Time Budget Pressure on Audit Quality (5) the effect of Due Professional Care, Objectivity, Audit Fee, Time Budget Pressure, on Audit Quality with Auditor Ethics as a moderating variable. Hypothesis testing is done by using multiple linear regression analysist, T test, F test. The results of this study indicate: Auditor Ethics is able to moderate the Due Professional Care relationship to Audit Quality, t count 2.554 with a significance value of 0.013. Auditor Ethics is able to moderate the objectivity relationship to Audit Quality, count 3.099 with a significance value of 0.002. Auditor Ethics is able to moderate the relationship of Audit Fee to Audit Quality, t-count 2.156 with a significance value of 0.035. Auditor Ethics is able to moderate the relationship of Time Budget Pressure to Audit Quality, count 2,018 with a significance value of 0.048.